Aplicação de Campo Magnético Contínuo em modelo de queimadura de segundo grau em roedores. - Lewandoski, Lizie Tanani (2024)
ntroduction: Burn it is a injury made for a external agent that promotes the breakup of tissue integrity. Constitutes a world healthy problem, because presents high rates of morbity and mortality. Thus, search new therapeutic modalities for this lesions that be affordable, painless, non-invasive, without adverse effects and easy use. Objectives: Investigate morphophysiological effects of the static magnetic field in second degree burn induzed on Wistar rats. Methods: Basic study, experimental character, quantitative and prospective approach. Were used 40 females of approximately 20 months of age, separated randomly into five groups. After a week of acclimatization happend the burn induction in the dorsum of each animal: then G1- control group, G2- silver sulfadiazine group, G3- 1200 Gauss magnets group, G4- 1800 Gauss magnets group e G5- 2500 Gauss magnets group. The treatment was apllied for two hours daily, within a period of five consecutive days, in all groups. Macroscopic assesment was realized 24 hours pos injury (ninth day), tenth day of experiment, twelfth day, fourtheent day before the euthanasia. In relation to macroscopic evaluation were analysed: wound area, weight, photothermometry and esthesiometry. Samples of injured and intact skin were collected after the sacrified for histological processment and slides manufacturing, that was stained with hematoxylin-eosin to analyse healing process and Pycrosirius Red to analyse the type and quantify of Collagen. Later mycroscopic analysis was performed with help of the software Image Pro Plus e Gimp 2.10.34. Statistic analysed by the program SPSS. Results: macroscopic analysis realized about the parameters: wound area, weight, temperature and esthesiometry, there was no difference between the control and intervention groups. Showing differences only the evaluated moments. Nonetheless about to thichkness of the epidermis: there was difference between G4 compared to others groups, and this group did not presents difference when compared to full skin. With G1, G2, G3 and G5 showing differences when compared to full skin, the G3 and G5 did not presented differences between G2 usual treatment. About the collagen deposicion between the groups: Conclusions: not dettected difference in the macroscopic analysis, wound size, temperature, esthesyometry and weight of treated animals, with static magnetic field compared to control group or usual treatment. Reepithelization analysis was observed significant increase in G4, and in the others Magnetic fields groups were similar to usual treatment group. In relation to collagen deposition it was noticed a delayed on wound healing in control group and similarity between the colagens indices of treatment G2 and G4. The others Magnetic Fields groups presented betters results than control group, but lower than G4 and G2. Thus its indicated static magnetic field to treat burns injuries, mainly in middle intensity (1800 G).